Les réservoirs de carbone en forêt boréale à l’est du Canada : acquis et incertitudes dans la modélisation face aux changements climatiques - Aurélie Terrier; Martin Girardin; Yves Bergeron (VertigO)
Climate change is of major concern for forest managers. The boreal forest is becoming increasingly central to discussions on carbon cycling because of its capacity to compensate for anthropogenic carbon emission. The boreal forest captures relatively small amounts of carbon in comparison to more temperate or tropical forests, due its cold climate and the short growing season. However, emission of carbon from dead matter decomposition is also slow, which can result in high levels of organic matter accumulation. Models suggest that the capacity of the boreal forest to capture carbon could increase in response to climate change but current models have too many uncertainties to be able to inform appropriate management decisions, including responses of boreal carbon sinks to climate change. Models are simplifications of complex natural systems and uncertainties arise from the lack of knowledge of all the processes in the system, many of which could be interacting. In this article, we first synthesize processes leading to carbon exchange between the forest and the atmosphere. Secondly, we present current knowledge of climate change impacts on carbon sinks in the boreal forest in eastern Canada. Finally, we discuss three types of uncertainties: the uncertainties in the data, structural uncertainties and unpredictable uncertainties, and we propose recommendations for reducing each type of uncertainties.